ENTREPRENEURIAL EDUCATION AS A COMPONENT OF THE EDUCATIONAL POLICY OF UKRAINE (Innovative professional education, 2024)
The publication highlights the results of the analysis of the state, goals and objectives of entrepreneurial education in Ukraine and its place in the European economic and educational space. Attention is drawn to the fact that the basis of educational policy in Ukraine includes elements of career guidance, informing about the labor market and active entrepreneurship training, consulting on youth entrepreneurship and job search, employment programs, public works and communal services, employment subsidies that ensure the implementation of programs preparation for entrepreneurial activity. In particular, the difference in methodological approaches to determining the role and importance of youth entrepreneurship counseling in Ukraine and the world is highlighted.
Keywords: entrepreneurship, entrepreneurial activity, career growth, entrepreneurial education, consulting method